The Purok System of San Francisco, Camotes: A Communication Perspective of Community-Based Haiyan Response - Ponce de Leon, Inez Z (Archīum Ateneo, 2021)
The Philippine government relies on a dissemination model to send out warning messages. This approach can disregard local subcultures if the message is generic, removes context from risk information, and is not cognizant of local capacity to respond to hazards. The municipality of San Francisco, Camotes, however, uses an alternative community-based model: the purok, which divides villages into smaller, independently-governed units. This model reportedly allowed the municipality to escape the devastation of Typhoon Haiyan. The researcher studied the implementation of the purok system during Haiyan using Hall's Encoding-Decoding theory, and traced how information traveled from municipal government to citizens. Through systematic qualitative analysis of focus group discussions and interviews, the researcher found that residents of a fishing village could contextualize generic warning information and use the information to spur action; however, they could not imagine the impact of more powerful storms. They also evacuated without waiting for the weather to worsen. Residents of a tourist center, on the other hand, simply disseminated generic information, but knew that context played a role in how people acted on warnings. They also waited for the weather to worsen before evacuating. These findings support previous research that criticizes the purok system as being top-down rather than empowering. This research provides a detailed, qualitative perspective to community-related factors derived from previous work based on surveys. This research also contributes to risk communication by providing empirically-grounded advice for how community-based approaches to natural hazards might be enhanced through greater community participation.